Physiological and lipidomic characterization of high temperature stress and traits associated with tolerance in wheat - Narayanan, Sruthi (Kansas State University, 2015)
High temperature is a major environmental factor that limits wheat productivity. Climate models predict greater increases in night temperature than in day temperature. The objectives of this research were to quantify the effects of high day and night temperatures during anthesis on physiological (chlorophyll fluorescence, chlorophyll concentration, leaf level photosynthesis, lipid peroxidation and membrane damage), biochemical (reactive oxygen species [ROS] concentration and antioxidant capacity in leaves) and yield traits and membrane lipid profile and identify the lipids that are associated with high temperature response in wheat. Winter wheat genotypes Ventnor (heat tolerant) and Karl 92 (heat susceptible) were grown at optimum temperatures (25/15°C, maximum/minimum) until the onset of anthesis. Thereafter, plants were exposed to high night (HN, 25/24°C), high day (HD, 35/15°C), high day and night (HDN, 35/24°C) or optimum temperatures. Compared with optimum temperature, HN, HD and HDN increased ROS concentration, lipid peroxidation and membrane damage and decreased antioxidant capacity, photochemical efficiency, photosynthesis, seed set, grain number and grain yield. Impact of HN and HD was similar on all traits, when stress was imposed for seven days. High day and night temperatures resulted in significant changes in the amount of plastidic and extra-plastidic lipids and lipids with oxidized acyl chains (ox-lipids) in both genotypes. The decrease in lipid unsaturation levels of complex lipids at high temperatures was predominantly due to decrease in 18:3 fatty acid and increase in 18:1 and 16:0 fatty acids. We identified novel odd-numbered long-chain fatty acid-containing phospholipids, which were highly responsive to high temperature stress. Ventnor had higher amounts of sterol glycosides (SG) and lower amounts of ox-lipids at high temperatures than Karl 92; thus SGs and ox-lipids may be potential biomarkers for heat tolerance and susceptibility, respectively, in wheat. Co-occurring lipids, which are up-or-down-regulated together through time under high day and night temperatures formed groups, which were experiencing coordinated metabolism. These results suggest that high day and night temperatures during anthesis cause damage of a similar magnitude to wheat, if stress is imposed for a short term (seven days) and compositional changes in lipid profile in response to high temperature contribute to heat tolerance.
Keywords: Wheat; Lipids; Photosynthesis; High temperature stress; High night temperature; Lipid co-occurance